Tetchie nanay makabagong nanay para sa ligtas na buhay. - Mamaasin Team; Azarraga, Alyssa Faye N.; Brazas, Jodelyn M.; Bordon, Jenn Margarette B. (2017.)
Maternal mortality is an alarming problem in the Philippines and is usually caused by non-facility based deliveries (NFBD). In 2013, the DOH reported that the province of Iloilo has the highest maternal mortality rate in Western Visayas, and Maasin is located in this province. Among the 50 barangays if Maasin, Brgy. Abay was chosen due to its high cases of NFBD. This study was conducted to improve the knowledge, attitude and practices (KAP) of women of reproductive age (WRA) towards maternal health and reduce the cases of non-facility based deliveries among pregnant women of Brgy. Abay, Maasin, Iloilo. The KAP of the WRA was improved through a series of lectures in a span of 4 weeks. In order to improve maternal health in Brgy. Abay, the team introduced a smartphone application called iNanay for the use of pregnant women and launched a web server database in the Rural Health Unit (RHU). Both components help in pregnancy monitoring. For the project sustainability, the mothers elected a core team called ?KaakABAY?. Smartphones were givento 6 pregnant women in Brgy. Abay and they were taught by the KaakABAY about the features of the application. Since ni delivery took place within the six-week immersion, the effectivity of the iNanay app was solely evaluated by tracking the attendance of the pregnant women to their prenatal check-ups that were scheduled within the time of immersion.
Community Project (Undergraduate, Bachelor of Science in Public Health) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, iloilo. 2017.
Keywords: Mothers